Two new species of Oobius (Hymenoptera: Encyrtidae) and their phylogenetic relationship with other congeners from northeastern Asia. Issue 3 (19th April 2018) - Yao, Yan-Xia; Duan, Jian J.; Mottern, Jason L.; Wang, Xiao-Yi; Yang, Zhong-Qi; Bauer, Leah S.; Gates, Michael W.
Abstract: Two new species of egg parasitoids, Oobius saimaensis Yao and Motternnew species and Oobius fleischeri Yao and Duannew species (Hymenoptera: Encyrtidae), are described from eggs of Agrilus fleischeri Obenberger, 1925 (Coleoptera: Buprestidae). Agrilus fleischeri is a phloem-feeding woodborer of poplar ( Populus Linnaeus; Salicaceae) in northeastern China. These two species can be distinguished morphologically as O. fleischeri has five tarsomeres and O. saimaensis has four tarsomeres. Although O. saimaensis is morphologically similar to its sympatric congener O. agrili Zhang and Hang, 2005, an important natural enemy of the invasive emerald ash borer, Agrilus planipennis Fairmaire, 1888, molecular phylogenetics and morphological data indicate that they are distinct species. Phylogenetic relationships among the new species and other closely related species are also inferred by using DNA sequence data from several ribosomal and mitochondrial genes. In addition, we expand the known distribution of Oobius primorskyensis Yao and Duan, 2016 to include South Korea.